Application of capacitive sensors to inverse problems in electrostatics - Prybytko, Maksym (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2003)
The electrostatic imaging problem is an inverse electrostatic problem Involving the reconstruction of an inhomogeneous dielectric medium from a set of remote electrostatic field measurements. In this thesis we propose and explore a novel application of a capacitive sensor array to the electrostatic imaging problem. The capacitive sensor array that investigate is composed of planar conducting electrodes located on and insulated from a wider ground plane. The analytical model of the planar capacitive sensor array is proposed to be a doublesided boundary.
Keywords: Electronic and Electrical Engineering, Ph.D.; Ph.D. Trinity College Dublin